The Principle of the Social Market Economy from the Perspective of Public Economic Law - Powałowski, Andrzej (Review of European and Comparative Law, 2023)
The social market economy is a conceptual category transposed to the provisions of the Constitution of the Republic of Poland, within which it is defined as a principle. It constitutes an appropriate foundation for the construction and functioning of the system of public economic law. It is a starting point for actions of the state and its bodies and defines the range of influence on the economy, as well as directs state activity in the economy. The premises for the participation and influence of the state on the economy which, according to the assumptions, should be both market-oriented and responsive to social needs, result from the principle of a social market economy. The objective so outlined should be pursued through the rules of public economic law and the legal constructions and institutions introduced in this normative area. They must remain, in terms of their content and nature, in close connection with the essence of the principle in question and its constituent elements.